2015
DOI: 10.2174/1573400510666141114223827
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Selected Musculoskeletal Late Effects in Survivors of Childhood Cancer

Abstract: Survivors of childhood cancer are at risk for treatment-related musculoskeletal late effects. Early detection and orthopedic intervention can help ameliorate musculoskeletal late effects and prevent subsequent complications. This systematic review summarizes the literature describing associations between cancer, its treatment, and musculoskeletal late effects. We searched PubMed and Web of Science for English language articles published between January 1970 and December 2012. The search was limited to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 122 publications
2
76
1
3
Order By: Relevance
“…These observations fit to previously published studies from UK where the evaluation of a General Practitioner database revealed a comparably increased risk of osteoporosis and diabetes, particularly in patients with non-Hodgkin disease. Interestingly, despite our expectations that children and adolescents would be more prone to develop late effects, especially of the bone, the frequencies of adult late effects observed in this study appear to be largely similar (5,27,28,29,30,31,32,33). There are a number of potential underlying mechanisms, which due to the nature of the study must remain speculative.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latecontrasting
confidence: 66%
“…These observations fit to previously published studies from UK where the evaluation of a General Practitioner database revealed a comparably increased risk of osteoporosis and diabetes, particularly in patients with non-Hodgkin disease. Interestingly, despite our expectations that children and adolescents would be more prone to develop late effects, especially of the bone, the frequencies of adult late effects observed in this study appear to be largely similar (5,27,28,29,30,31,32,33). There are a number of potential underlying mechanisms, which due to the nature of the study must remain speculative.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latecontrasting
confidence: 66%
“…Though TBI and HSCT allow for reduced early mortality and improved long‐term survivorship, they are associated with several acute and late‐onset toxicities . Important musculoskeletal complications are summarized in Supplementary Table S1 and include short stature, physeal damage, angular deformities, reduced bone mineral density (BMD), vertebral fractures and deformity, osteonecrosis, SCFE, and the development of benign or malignant tumors …”
Section: Total Body Irradiation and Hematopoietic Stem Cell Transplanmentioning
confidence: 99%
“…The effect of irradiation on the spine is multifactorial and related to both direct effects on the bone itself as well as endocrine derangements . Though loss of standing height is better documented, sitting height is affected to a greater extent .…”
Section: Short Stature and Abnormal Growthmentioning
confidence: 99%
See 2 more Smart Citations